(untitled) (Anclajes, 2022)
We propose to read Los Sorias, by Alberto Laiseca, as a long duration’s fiction and practice. This means addressing the knowledge about time, formal and common, that the novel promotes from various images and that define doing time as a very slow practice (of reading, writing, publishing), supported by Alberto Laiseca. This, in addition, is articulated with the conception of the novel as a time machine, from which Laiseca defines a very slow duration with the past as an open time.